Percepções de desigualdade no trabalho a partir de uma perspectiva de gênero: relatos das trabalhadoras de uma grande transnacional do varejo - Almeida, Bruna Lyra Alves de (2012)
The present study aims to examine women's perceptions about their working conditions in a large chain of transnational supermarkets installed in Brazil during trade liberalization in the 1990s. For this goal to be achieved it was necessary the theoretical background about the sexual division of labor, present throughout the history of women's work, and the understanding of the changes which occured in the world of work that developed the phenomenon of precariousness and labor flexibility. The retail supermarket segment suffered the impacts of the flexibility and precariousness unleashed in the labor world, that reflected in the introduction of technological innovations and the policy of reducing operating costs. These changes impacted the worker, as, the studied firms have adopted a management philosophy based on the toyotist model, as horizontalization, downsizing, Just in time, polyvalence and teamwork. The adoption of new processes and ways of managing gave the companies more scope to explore the workforce, increase the working hours and manipulate the worker to their interests. The women s situation, in this context, was the focus of this research, once their womanhood is associated to different aspects of discrimination and inequalities both in production and in the reproductive sphere. They always faced more challenges than men to consolidate in the labor market and are the most concentraded on precarious occupations. This study was delineated by a qualitative research whose case study was conducted in a multinational grocery business, known for adopting tough policies against competition, which operates in 18 states of Brazil. Fifteen women who worked or work at stores of the analyzed company, located in the great João Pessoa were interviewed. It was proved that, through the interviews made that perceptions of unequal gender perspective are contradictory in the sense that the talks induce the manipulated speech of the company, however, experiments show a strong impact scenario of working flexibility policies and extreme exploration of the worker, a fact that is more threatening for women, who face the double day wear and prejudice and discrimination in their professional context.